The Effect of Job Passion on Innovative Work Behaviors: Analytical Research in the Ministry of Higher Education and Scientific Research - Ghafil Jawad Al Issawi, Hasan; Hassoon AlTaee, Ali (Journal of Economics and Administrative Sciences, 2024)
The current research aims to test the impact of Job passion on innovative work behaviors, and the idea of the research revolves around providing a job passion that contributes and supports the innovative work behaviors among the employees of the Ministry of Higher Education and Scientific Research, as the job passion variable includes four dimensions (enjoyment at work, self-motivation, self-identity, and a sense of learning). The innovative work behavior variable has addressed four dimensions (the ability to provide creative solutions to problems, the ability to new ideas and proposals, the ability to change as well as initiate, and the spirit of risk), A sample of the employees of the Ministry of Higher Education and Scientific Research, where a random stratified sample of 328 employees were selected from the study community (2229) relied on the questionnaire for collecting data, and the questionnaires valid for statistical analysis were 322 questionnaires. The research used a number of statistical methods to obtain the results of the questionnaire, especially the simple correlation coefficient (Pearson) and descriptive analysis methods using the SPSS.v23 and  AMOS.v23). It has proved the validity of the hypotheses through which a set of results were reached, the most prominent of which is the existence of a relationship between the impact of job passion and its dimensions on innovative work behaviors. The dimensions of the variable of innovative work behaviors above are available, but they do not be at the required level, where the ability to change and generate creative solutions. This requires focusing on them in addressing problems and making appropriate decisions that are based on a correct scientific basis, and the management's view of employees is not limited because they represent essential capabilities and tools for implementing decisions and policies.Paper type: Research paper.